A challenge to American pragmatism: staging O’Neill’s Hughie by Alexa Visarion - Bulz, Adriana Carolina (Swedish Journal of Romanian Studies, 2019)
“Hughie or the Tale of a Memory” is the working title of the first play that the experienced artist Alexa Visarion has directed for the independent theater (a production released in 2017). The purpose of my paper, which is an investigation of several drama reviews that discuss the play’s first night, is to prove that – despite difficulties with cultural reception and public taste (given a text by O’Neill that is 80 years old, as well as the director’s first time with an informal theater production) - this performance was a succesful attempt at communicating and debating the conflicted values of American pragmatism and equally a crowning of the Romanian director’s effort to stage O’Neill’s plays in our country. Relying on insights from the American doctrine of Pragmatism, I will try to show how O’Neill’s text challenges philosophical premises that are inbred in the American status-quo, thereby making his plays “anti-materialistic” by promoting a fatalistic approach to existence.